A Comparison of Note Writers and No Note Writers in Homicide-Suicide Cases in Germany. Issue 1 (2nd January 2018) - Weeke, Anna; Oberwittler, Dietrich
Abstract : The aim of this study is to investigate potential differences between homicide-suicide cases in which the perpetrator does or does not write a suicide note. As homicide-suicides are complex types of lethal violence for which the aggressor cannot be held accountable, suicide notes may be a valuable source of information about the background of these cases and the perpetrators' motives. We use a national sample of N = 288 homicide-suicide cases in Germany applying group comparisons and chi-square tests for relevant variables. Perpetrators killing their own children and perpetrators leaving children behind before killing themselves write significantly more suicide notes than other perpetrators. Even though note writers and no note writers are similar regarding most sociodemographic characteristics, other differences question the generalizability between these 2 groups.